Long Term Sediment Modification Effects after Applications of P Inactivation Method in Meromictic Lake (Starodworskie Lake, Olsztyn Lakeland, Poland) - Renata Augustyniak; Renata Tandyrak; Michał Łopata; Jolanta Grochowska (Land, 2021)
Lake restoration is a part of geoengineering, which is a useful tool for landscape management. The phosphorus inactivation method is one of the most popular lake restoration methods. Using chemical compounds for P binding is leading to the creation of sediment “active layer”, which should show higher P adsorption abilities, compared to non-modified sediment. Howewer, it provides rather little information, how long the modified sediment remains active, and whether it is effective in continuous P binding. Lake meromixis is not commonly observed phenomenon, and sediment located in monimolimnion area is subjected long term anoxia. Therefore, observation of “active layer” in a meromictic lake can give very important data about durability of restoration effects. The object of our study was meromictic Starodworskie Lake (5.57 ha, max. depth 24.5 m), located in Olsztyn Lakeland, Poland. In the past the analyzed lake was subjected to various restoration methods, and phosphorus inactivation method by alum use (1994–1995) was the last used treatment type. The mixing regime of this lake had changed from bradimictic (before and during restoration time) into durable meromictic (post-restoration period). The research made two decades after implementing of P inactivation showed the presence of “active” sediment layer 10–15 cm below sediment surface. This sediment layer showed much higher content of P bound to aluminum, compared to surficial sediment layer. P binding molar ratio was assessed and amounted to 16.1 straightly after restoration and 6.1 after 21 years. This fraction amounts were higher that the values noted before restoration (ca. 358% higher than in 1994) and during restoration (ca. 86% higher than in 1995), which was probably the effect of continuous phosphorus adsorption by “active layer” in post-restoration period.